Bio-Functional Aspects of Grape Seeds-A Review - Poonam Arora; S. H. Ansari; Iram Nazish (International Journal of Phytomedicine, 2010)
Grapes are one of the most widely consumed fruits all over the world and have considerable importance for their medicinal and nutritive value for thousand of years. Grapes are rich in polyphenols and 60- 70 % of grapes polyphenols exist in grape seeds. The seeds contain lipid, proteins, carbohydrates and 5-8 % polyphenolic compounds. The phenolic compounds present in grape seeds are flavonoids including gallic acid, flavan-3-ol monomers and their oligomeric and polymeric derivatives (procyanidins). The most abundant flavan-3-ol monomers isolated from grape seeds are Catechin, epicatechin, epicatechin-3-O-gallate, and epigallocatechin-3-O-gallate. Three novel flavan oxidative derivatives named viniferones A, B and C have also been isolated from grape seeds. The grape seeds are chiefly known for their significant antioxidant properties. Scientific studies have claimed that the antioxidant potential of grape seeds proanthocyanidins is 20 times greater than vitamin E and 50 times greater than vitamin C. Grape seeds polyphenolic (Proanthocyanidin) extract have been marketed in France for decades as treatment for venous and capillary disorders (e.g., retinopathies, venous insufficiency, and vascular fragility. Recent studies have shown that procyanidins in grape seeds possess antiinflammatory, anti-arthritic, anti-allergic effects and prevent heart diseases and skin aging. The high purity grape seed extract should contain polyphenols NLT 95% and monomers NLT 10%; and the grape seed extract with ordinary quality should have a procyanidolic value NLT 95%, and monomer NLT 6%.